2021
DOI: 10.3390/su13052746
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Impact of Uncertainty on R&D Investment: International Evidence

Abstract: Previous studies have not provided consistent conclusions regarding the impact of uncertainty on research and development (R&D) investment. While most of the previous literature has focused only on one or a small group of countries, this study examines the effect of uncertainty on R&D on the basis of a sample covering 109 countries from 1996 to 2018. The country-level uncertainty is measured using the “World Uncertainty Index”, which has recently been developed by Ahir et al. (2018). By estimating a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…However, R&D expenditure doesn't always produce similar effects on developments [15], as the study found negative relationship between R&D expenditure and SDG 8 among countries in South America, Australia, China, India, Oceania and the Middle East. Furthermore, [46] found negative effects between R&D expenditure and economic growth among several countries, globally. Zhu et al, [9] argue that when R&D expenditure is highly financed by government the effect on companies and firm's growth tends to be lower as they are guided by PLOS ONE governmental pressure.…”
Section: Plos Onementioning
confidence: 99%
“…However, R&D expenditure doesn't always produce similar effects on developments [15], as the study found negative relationship between R&D expenditure and SDG 8 among countries in South America, Australia, China, India, Oceania and the Middle East. Furthermore, [46] found negative effects between R&D expenditure and economic growth among several countries, globally. Zhu et al, [9] argue that when R&D expenditure is highly financed by government the effect on companies and firm's growth tends to be lower as they are guided by PLOS ONE governmental pressure.…”
Section: Plos Onementioning
confidence: 99%
“…19 Against that evidence, firm-level uncertainty may raise R&D investment because firms want to utilize R&D investment as a strategy to reach a competitive position. 20 Despite the conflicting views, the general consensus is that the direction of the impact depends mostly on a firm's learning curve in adjusting to changing market conditions. 10,21 Another relevant branch of literature focuses on strategic interaction between firms to explain the investment decisions under uncertainty using the real option model in the framework of a game approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…19 Against that evidence, firm-level uncertainty may raise R&D investment because firms want to utilize R&D investment as a strategy to reach a competitive position. 20 Despite the conflicting views, the general consensus is that the direction of the impact depends mostly on a firm's learning curve in adjusting to changing market conditions. 10,21…”
Section: Introductionmentioning
confidence: 99%